Systemic lupus erythematosus–associated diffuse alveolar hemorrhage: a single-center, matched case–control study in China - Sun, Yiduo; Zhou, Cong; Zhao, Jiuliang; Wang, Qian; Xu, Dong; Zhang, Shangzhu; Shen, Min; Hou, Yong; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng (Lupus, 2020)
Background This study described clinical characteristics and outcome in systemic lupus erythematosus (SLE) patients with diffuse alveolar hemorrhage (DAH), and investigated risk factors and prognostic factors for DAH. Methods We conducted a retrospective nested case–control analysis in a single-center cohort. We enrolled 94 SLE patients with DAH. For each case of DAH, two age-, sex-, and SLE courses–matched controls were randomly selected from our cohort. All patients were enrolled between 2004 and 2019 and were followed until death, end of registration with the physician’s practice, or end of January 2019. We estimated the risk factors for DAH and prognostic factors for mortality using multivariate analysis. Results We included 4744 patients diagnosed with SLE, with 94 cases of DAH, for an incidence rate of 2.0%. DAH may occur in any stage of SLE but mostly in the early phase of disease course. Lupus nephritis (LN) was the most common concomitant involvement at DAH diagnosis. By multivariate analysis, LN, anti-SSA positivity, thrombocytopenia and elevated C-reactive protein (CRP) were significantly associated with DAH in SLE patients. All-cause mortality was increased in SLE with DAH compared with SLE without DAH (adjusted hazard ratio 6.0, 95% confidence interval 2.8–13.0, p < 0.0001). Intravenous cyclophosphamide (CTX) showed an increased tendency for better survival in DAH after adjusting for Systemic Lupus Erythematosus Disease Activity Index 2000, acute kidney injury and mechanical ventilation. Conclusions LN, anti-SSA positivity, thrombocytopenia and elevated CRP were independent risk factors of DAH in lupus patients. Due to a high early death rate of DAH and little long-term damage, DAH patients may benefit from early diagnosis and intensive treatment, and CTX-based therapy can be a preferential choice.